Protective Role of Hepcidin in Polymicrobial Sepsis and Acute Kidney Injury - Scindia, Yogesh; Wlazlo, Ewa; Leeds, Joseph; Loi, Valentina; Ledesma, Jonathan; Cechova, Sylvia; Ghias, Elizabeth; Swaminathan, Sundararaman (Frontiers in Pharmacology, 2019)
Background: Acute kidney injury (AKI) portends worse prognosis following sepsis, with limited available interventions. Host iron acquisition by pathogens and systemic inflammatory response are key events in the pathogenesis of sepsis. In sepsis, hepcidin induces iron sequestration to limit iron availability to pathogens. Hepcidin is also known to limit inflammation. Since its role in pathophysiology of sepsis-associated AKI is unknown, we investigated the effect of exogenous hepcidin in endotoxin- and peritonitis-induced pathology and AKI. Methods: C57BL/6 mice were treated with saline or 50–100 µg of hepcidin, pre- and post-LPS injection, or cecal ligation and puncture (CLP, model of peritonitis). Splenectomized mice were challenged with LPS, with and without hepcidin. Mice were euthanized at 24 h after LPS injection and at different time points after CLP. Systemic inflammation and renal injury markers were assessed. Direct effect of hepcidin on renal tubular and endothelial cells was evaluated using endotoxin-induced cytotoxic serum. Role of heavy chain ferritin (H-ferritin) in mediating hepcidin-induced anti-inflammatory effect on LPS stimulated macrophages was evaluated with siRNA studies. Results: Twenty-four hours pretreatment with hepcidin significantly reduced LPS-induced AKI. Hepcidin ameliorated LPS-induced increase in serum TNFα and renal Cox-2, and prevented loss in PGC1α and cytochrome c oxidase activity. This was associated with reduced glomerular injury and preserved mitochondrial structure. Hepcidin did not exert direct protection on the renal parenchymal cells but reduced endotoxin-induced serum cytotoxicity to mitigate renal injury. Splenectomy reduced LPS-induced early inflammation and AKI, independent of hepcidin, indicating the importance of systemic inflammation. Higher splenic H-ferritin in hepcidin-treated animals was associated with reduced splenocytes apoptosis and inflammation. Hepcidin reduced LPS-induced IL-6 secretion in macrophages in H-ferritin dependent manner. Hepcidin significantly reduced CLP-induced AKI, and mortality (20% hepcidin treated vs 80% PBS treated). Importantly hepcidin reduced bacteremia and AKI even when administered after onset of sepsis. Conclusion: We demonstrate a protective role of hepcidin in endotoxin- and peritonitis-induced pathologies and AKI, exerted primarily through its anti-inflammatory effects, and antibacterial property. Macrophage H-ferritin plays an important role in hepcidin-mediated protection against endotoxin-induced inflammation. We uncover a novel prophylactic and therapeutic role of hepcidin in sepsis-associated bacteremia, AKI, and mortality.